Influence of final state interactions in attosecond photoelectron interferometry - S. Luo; R. Weissenbilder; H. Laurell; R. Y. Bello; C. Marante; M. Ammitzböll; L. Neoričić; A. Ljungdahl; R. J. Squibb; R. Feifel; M. Gisselbrecht; C. L. Arnold; et al. (Physical Review Research)
Fano resonances are ubiquitous phenomena appearing in many fields of physics, e.g., atomic or molecular photoionization, or electron transport in quantum dots. Recently, attosecond interferometric techniques have been used to measure the amplitude and phase of photoelectron wave packets close to Fano resonances in argon and helium, allowing for the retrieval of the temporal dynamics of the photoionization process. In this work, we study the photoionization of argon atoms close to the 3s^{1}3p^{6}4p autoionizing state using an interferometric technique with high spectral resolution. The phase shows a monotonic 2π variation across the resonance or a nonmonotonic less than π variation depending on experimental conditions, e.g., the probe laser bandwidth. Using three different, state-of-the-art calculations, we show that the measured phase is influenced by the interaction between final states reached by two-photon transitions.